Global Environmental Governance Social-Ecological Perspectives - Bruckmeier, Karl (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book provides a critical review of global environmental governance as part of the broader process of sustainably transforming modern society. The author argues for substantial modifications, outlining potential improvements in knowledge bridging processes, integration and synthesis that offer valuable information for environmental policy and governance. These improvements, he argues, should be achieved through the use of theoretical and empirical knowledge gleaned from global scenario analysis and interdisciplinary environmental research, and with the aid of new practices for knowledge sharing, cooperation and collective learning. The analysis presented in the book is based on recent developments in social ecology and the author's interdisciplinary theory of society-nature interaction (Social-Ecological Transformation: Reconnecting Society and Nature, Palgrave Macmillan, 2016).